The renaissance vihuela's impact on contemporary classical guitar education - Curto, Romeu (2024)
The article presents a compelling argument for the revival of the vihuela’s repertoire in modern classical guitar pedagogy. This resurgence is not merely a nod to historical curiosity but a pedagogical strategy that enriches stu- dents’ musical education by bridging technical and expressive skills with a deep understanding of musical heritage. The inclusion of the vihuela’s repertoire offers a unique blend of challenges and opportunities, enabling students to engage with complex polyphonic textures, intricate techniques, and expressive depths rooted in the Renaissance tradition. The comparative analysis with contemporary instruments and pedagogical materials underscores the vihuela’s unique contribution to developing a well-rounded musical education that honors the past while engaging with the present. This article sets the stage for future research, advocating for a broader integration of historical repertoires into classical guitar education, thereby expanding the pedagogical landscape and enhancing the educational experience for students.